Application of Technology Artificial Intelligence in Claim Settlement at PT. Asuransi Allianz Life Syariah Medan Branch - Fachrunisa Winda Marpaung; Nuri Aslami; Ahmad muhaisin B. Syarbaini (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This research aims to analyse the effectiveness of implementing artificial intelligence (AI) technology in accelerating the settlement process of Sharia insurance claims at PT Asuransi Allianz Life Syariah Medan Branch. The main focus of this research is to measure the impact of AI technology on customer satisfaction and the company's performance in handling Sharia insurance claims. Using qualitative research methods, data were collected through in-depth interviews with company representatives and analysis of the company's internal documents. The research results indicate that AI technology has significantly contributed to improving operational efficiency, speed, and accuracy in claim resolution. The implementation of AI enables more effective process automation, faster decision-making, and more accurate identification of potential fraud. Furthermore, the use of AI also supports the enhancement of compliance with Sharia principles, ensuring that all processes and decisions are in line with Sharia law. This research provides valuable insights for insurance companies looking to implement AI technology in their operations, particularly within the scope of Sharia insurance.